Impacto nutricional da infusão ruminal de níveis de glicerina bruta em ovinos alimentados com forragem - Zeni, Diego (2013)
The aim of this study was to evaluate the impact of rumen infusion levels (0, 0.5, 1.5 and 3 ml / kg body weight (BW)) of crude glycerin (CG) on intake and digestion by sheep fed tropical or temperate forage . Two experiments were conducted in a double 4x4 Latin square each with eight Corriedale breed sheep (26 ± 3 kg BW), cannula implanted with ruminal and duodenal probe. In one of the experiments the animals were fed oats and the other of Tifton. A third test was performed to measure the rate of disappearance of glycerol in the rumen. No significant interaction with treatment diet for most of the variables analyzed. Ruminal infusion of CG linearly reduced forage intake, ruminal pH and ammonia N concentration in ruminal fluid, but no effect on ruminal digestibility or total organic matter, neutral detergent fiber and nitrogen compounds. Similarly, linearly decreased urinary and fecal excretion of N, as well as the amount of α-amino N which flowed into the duodenum, but did not affect the retention of N. The duodenal flow of microbial N was similar in all treatments when estimated by purine derivatives in the urine, but was negatively affected by the CG when estimated by purines in duodenal digesta. Regardless of the label used, the efficiency of microbial protein synthesis was not affected by CG. The duodenal flow of N and not microbial no ammonia (NNANM) as well as the proportion of degradable protein in their diet, were affected by treatment interaction with type of material. In animals fed with oats NNANM duodenal flow increased linearly, whereas those fed Tifton decreased linearly with increasing ruminal infusion of CG. As a result, the proportion of the protein degraded in the rumen linearly decreased when the diet was oats, and tended to increase when the diet was Tifton, particularly at the highest dose of CG. Less than 1% of the glycerol infused into the rumen reached the small intestine. In conclusion, the presence of CG in the rumen of animals fed forage, regardless if it is tropical or temperate grass, dramatically lowers the supply of amino acids and digestible energy, mainly by reducing forage intake.